Application of the W index of free living nematode communities for rapid assessment of sedimentary environment quality in the Sai Gon river - Yen, Nguyen Thi My; Thai, Tran Thanh; Thao, Nguyen Thi Phuong; Nghia, Nguyen; Quang, Ngo Xuan (Vietnam Journal of Marine Science and Technology, 2019)
The W index of nematode communities was first applied to assess sedimentary environment quality at 12 stations in the Sai Gon river. The nematode samples were collected and examined during the dry and rainy seasons in 2014. The W results indicated considerable disturbance in the downstream stations of the Sai Gon river that is mainly disturbed by harbour activities. The nematode communities in these harbours such as the Bien Dong port, Lotus port and Navioil port areas have been seriously impacted in both seasons. In the rainy season, the sedimentary environment of the Tan Thuan Dong port, Sai Gon New port was disturbed significantly while that was lightly affected in Ben Nghe port, Vietnam International Container Terminals - VICT port and Ben Duoc - Cu Chi stations.